Let's expand the expression \((4x + 3)(-3x^2 - 5x + 10)\) and then combine like terms.
First, we will distribute \((4x + 3)\) across each term in \((-3x^2 - 5x + 10)\).
-
Distributing \(4x\) across \((-3x^2 - 5x + 10)\):
- \(4x \cdot (-3x^2) = -12x^3\)
- \(4x \cdot (-5x) = -20x^2\)
- \(4x \cdot 10 = 40x\)
-
Distributing \(3\) across \((-3x^2 - 5x + 10)\):
- \(3 \cdot (-3x^2) = -9x^2\)
- \(3 \cdot (-5x) = -15x\)
- \(3 \cdot 10 = 30\)
Now, we will combine all the terms from the two distributions:
- The \(x^3\) term: \(-12x^3\)
- The \(x^2\) terms: \(-20x^2 - 9x^2 = -29x^2\)
- The \(x\) terms: \(40x - 15x = 25x\)
- The constant term: \(30\)
Putting it all together, we get the polynomial in standard form:
\[ -12x^3 - 29x^2 + 25x + 30 \]
So the final answer, in standard form, is:
\[ -12x^3 - 29x^2 + 25x + 30 \]